A metabolomic study of adipose tissue in mice with a disruption of the circadian system1. Issue 7 (16th July 2015) - Castro, C.; Briggs, W.; Paschos, G. K.; FitzGerald, G. A.; Griffin, J. L.
<x xml:space="preserve">Abstract</x> Metabolomics has been used to analyse adipose tissue in mice with an adipocyte-specific deletion of Arntl, showing the importance of the peripheral circadian clock in metabolic regulation. Arntl induces global changes in both white and brown adipose tissues which were distinct for the two tissues.